CHANGING NATURE OF STATE POLITICS OF RAJASTHAN - Meena, Harsh (International Journal of Research -GRANTHAALAYAH, 2025)
The state politics of Rajasthan is unique in that after every Assembly election, the government changes in an alternative manner of political parties. For the last three decades, the incumbent government has never succeeded in retaining the power. However, the core competitors for political power are the INC and BJP. The current paper will explore why Rajasthan has developed such a unique trend of the Bi-party system, its smooth shift to a dominant party system following the national trend between 2014 and 2023, and its further transition from dominant party to Bipolar competition. The 2014 election led to a return to a dominant party era, with BJP replacing Congress nationally. However, at the level of State Assembly elections, the power keeps oscillating between Congress and BJP. Still, at the Lok Sabha level from 2014 to 2019, the BJP has had massive domination over all of the parliamentary seats in Rajasthan. Interestingly, even at the Assembly level, power oscillated, but the total vote share percentages of Congress reduced drastically along with the reduction of seats won in every Assembly election. These trends show that the BJP has successfully maintained a dominant Party system in Rajasthan. However, the verdict of the 2024 Lok Sabha election has created a break in this decadal trend and restructured the party competition of Rajasthan back to its pre-2014 Bipolar competition.